Risques sanitaires lies aux composés chimiques contenus dans l'eau de boisson dans la ville d'El Oued.Cas des ions nitrates et phosphates - المكي, حمايدي; لخضر, بن داود (University of El-Oued, 2020)
"Through what has been studied about the problem of groundwater pollution with nitrates and phosphates in the northern region of Oued Souf, especially in terms of health effects. Accordingly, the analyzes were performed in Al-Shehabi's laboratory. In order to assess the quality of this water at the level of the specified area, laboratory analyzes were conducted by cutting samples from 10 wells. The mineral quality of the groundwater at the level of the study area showed that the concentration of nitrates and phosphates was average, i.e. from 18 to 26 mg / l for nitrates, as for phosphates from 0.4 to 2.9 mg / l. These results are ideal compared to the standards documented by the World Health Organization "من خلال ما تم دراسته حول مشكل تلوث المياه الجوفية بالنترات والفوسفات في الإقليم الشمالي لمنطقة وادي سوف وخاصة من حيث الآثار الصحية. وبناء على ذلك تم إجراء التحاليل في مخبر الشهابي. وبهدف تقييم نوعية هذه المياه على مستوى المنطقة المحددة تم إجراء تحاليل مخبرية باقتطاع عينات من 10 آبار. النوعية المعدنية للمياه الجوفية عل مستوى منطقة الدراسة بينت أن نسبة تركيز النترات والفوسفات كانت متوسطة أي من 18 إلى 26 ملغ /ل بالنسبة للنترات أما الفوسفات من 0.4 إلى 2.9 ملغ/ل وهذه النتائج تعد مثالية مقارنة بالمعايير الموثقة من طرف منظمة الصحة العالمية
مذكرة ماستر تخصص Conception et Diagnostic des systèmes d'AEP et d'assainissement
Keywords: المياه الجوفية - التلوث - وادي سوف –الفوسفات - منظمة الصحة العالمية; Groundwater - Pollution - Wadi Souf - Phosphates - World Health Organization